The Role of School Education in Promoting Moral Values among Students at Secondary Level - Um E Rubab; Ahmed, Zaheer; Bano, Asia (ACADEMIA International Journal for Social Sciences, 2026)
The study titled “The Role of School Education in Promoting Moral Values among Students at Secondary Level” investigates the contribution of formal schooling to the moral development of students during a critical stage of their educational journey. It emphasizes the importance of fostering ethical values such as honesty, respect, and responsibility through structured educational practices and school environments . The objectives of the study were to examine the role of school education in promoting moral values, analyze the influence of classroom environment and school culture on moral development, and investigate the effectiveness of curriculum and teaching practices in inculcating moral values. The study adopted a quantitative research design using a descriptive survey approach. The population comprised approximately 320 secondary schools and 48,000 students in District Rawalpindi, while a sample of 20 schools and 200 students was selected through stratified random sampling technique. A structured questionnaire based on a five-point Likert scale was used as the research tool. Content validity was ensured through expert review, while reliability was confirmed through a pilot study with a Cronbach’s Alpha value of 0.82. Data were analyzed using descriptive and inferential statistics, including mean, standard deviation, t-tests, and correlation through SPSS. The findings of the first objective revealed that school education plays a significant role in promoting moral values, with a high overall mean score (4.08), particularly highlighting the role of teachers in shaping ethical behavior; therefore, it is recommended that teachers should be further trained to effectively integrate moral values into their teaching practices. The study is significant as it provides empirical evidence for policymakers, educators, and administrators to enhance moral education practices, improve curriculum integration, and foster positive school environments to develop ethically responsible citizens.